Pengaruh Ekstrak Etanol Daun Vernonia amygdalina, Del terhadap Kadar Kreatinin Serum Mencit Putih Jantan - Suryati Suryati; Dwisari Dillasamola; Fridhani Rahadiant (Fakultas Farmasi Universitas Andalas, 2016)
Vernonia amygdalina, Del leaves which are locally known as Afrika Selatan leaves used as traditional medicine for diabetes, fever, hypertension and uric acid. A study on the effect of their ethanolic extract on serum creatinin level of male white mice has been done. A twenty of male white mice were divided into four groups which were control group and three test group (A, B, C) which given extract with dose 100 mg/kg BW, 200 mg/kgBW and 400 mg/kgBW respectively. Test group were given extract orally for 21 days. The mice neck was cut and their blood collected at 7th, 14th and 21st day. The serum creatinin level was measured by using spectrophotometer UV-Visible at 492 nm. The result showed all doses of ethanolic extract gave statistically difference on the serum creatinin level (p<0.05). The doses at 400 mg/kgBW showed the most effective in reducing serum creatinin level.